2010
DOI: 10.1103/physrevb.82.033306
|View full text |Cite
|
Sign up to set email alerts
|

Spatially correlated microstructure and superconductivity in polycrystalline boron-doped diamond

Abstract: Scanning tunneling spectroscopies are performed below 100 mK on polycrystalline boron-doped diamond films characterized by transmission electron microscopy and transport measurements. We demonstrate a strong correlation between the local superconductivity strength and the granular structure of the films. The study of the spectral shape, amplitude, and temperature dependence of the superconductivity gap enables us to differentiate intrinsically superconducting grains that follow the BCS model, from grains showi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 26 publications
5
32
1
Order By: Relevance
“…2, the superconducting gap in the density of states is gradually suppressed with increase of temperature and the estimated superconducting critical temperature T c = 7 ± 0.5 K. Such measurements were performed at numerous locations across the sample surface, yielding identical results within experimental error. We did not observe any spatial variation of SDOS as reported in previous studies of polycrystalline boron doped diamond [11][12][13][14]. Notably, the value of the differential conductance inside the superconducting gap is equal to zero (see Fig.…”
Section: O Onufriienko Et Alsupporting
confidence: 58%
See 1 more Smart Citation
“…2, the superconducting gap in the density of states is gradually suppressed with increase of temperature and the estimated superconducting critical temperature T c = 7 ± 0.5 K. Such measurements were performed at numerous locations across the sample surface, yielding identical results within experimental error. We did not observe any spatial variation of SDOS as reported in previous studies of polycrystalline boron doped diamond [11][12][13][14]. Notably, the value of the differential conductance inside the superconducting gap is equal to zero (see Fig.…”
Section: O Onufriienko Et Alsupporting
confidence: 58%
“…3). This is in steep contrast with previous studies on polycrystalline samples [11][12][13][14]. To our knowledge, such homogeneous hard gap was observed only in the case of a single crystal [15].…”
Section: O Onufriienko Et Alcontrasting
confidence: 54%
“…The former indicated that diamond valence-band holes establish the Fermi surface of BDD, thus rendering a possible impurity-band scenario unlikely. STM data revealed that Si:B epilayers exhibit BCS-like superconductivity [13] while in nanocrystalline BDD the proximity effect has been found [14,15]. A distinct carbon but less clear boron isotope effect has further unraveled the phonon-mediated nature of superconductivity in BDD [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…That is why further insight in microstructure and local analysis is highly desirable. Most important recent work include angle-resolved photo-emission spectroscopy [12] and low-temperature scanning tunnelling microscopy (STM) [13][14][15]. The former indicated that diamond valence-band holes establish the Fermi surface of BDD, thus rendering a possible impurity-band scenario unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…2 An unusual property of metallically doped NCD films is its superconductivity at low temperatures, as shown in Figure 14.7. 5,[15][16][17][18][19][20] The resistivity of NCD increases with decreasing temperature above the critical temperature (T c ), in contrast with metallically doped single crystal diamond. The T c is around 2 K in this case; however, higher values have been reported since this work.…”
Section: Carrier Transport In Ncd Filmsmentioning
confidence: 98%